Hubungan Citra Merek Dan Kompetensi Komunikasi Customer Service Terhadap Loyalitas Konsumen Produk Indihome - Amalia Ardi, Fasya; Widowati Herieningsih, Sri (Interaksi Online, 2018)
The development in the telecommunication industry in Indonesia is so fast, whether viewed from internet users or telecommunications service providers. The intense competition for consumer loyalty in the telecommunication industry business, especially in Semarang, is also due to the increasing number of telecommunication industry businesses emerging and entering the market area such as MyRepublic service, Biznet, Indihome, Ooredoo GIG, MNC Play Media, Biznet, First Media and Indovision . This study aims to determine the relationship between brand image and customer service communication competence to consumer loyalty Indihome products PT. Telkom Indonesia Witel Semarang. Result of research from correlation test of Kendall Tau b explains that brand image with consumer loyalty product Indihome PT. Telkom Indonesia Witel Semarang produces a value of 0.000 significance and correlation coefficient value of 0.537. This can be interpreted that both variables have a positive relationship and the closeness of the relationship between the two variables are quite strong. Meanwhile, the results of customer service communication competence with consumer loyalty Indihome products PT. Telkom Indonesia Witel Semarang produce significance value 0,003 and correlation coefficient value 0,312. This can be interpreted that there is a significant relationship between the two variables and quite tightly. With these results suggested to the company Indihome PT. Telkom Indonesia Witel Semarang further enhances the communication competencies of customer service, especially on indicators of knowledge that are still perceived as less by consumers.